Odpowiedzi

2010-03-20T10:34:44+01:00
A )
4 - 2x -x-3 = x-5 -3 - x
-2x -x -x -x = -5 -3 - 4 +3
-5 x = -9 / -5
x = 9/5 (ułamek)
x = 1 całość 4/5
1 5 1
2010-03-20T10:41:06+01:00
A)(4-2x)-(x+3)=(x-5)+(-3-x)
4-2x-x-3=x-5-3-x
4-3x-3=-8 /+3
4-3x=-5/-4
-3x=-9/:(-3)
x=3


b)(3-2x)-(x-4)=-(3-2x)+(5x+4)
3-2x-x+4=-3+2x+5x+4
7-3x=1+7x /+3x
7=1+10x /-1
6=10x /10
x=6/10=0,6

c)-(x+3)+(2x-1)=(1+4x)+(3+x)
-x-3+2x+1=1+4x+3+x
x-2=4+5x /-x
-2=4+4x /-4
-6=4x /:(-4)
x=-1,5

d)-(x+3)-(2x+8)=(-3-2x)+(2x+1)
-x-3-2x-8=-3-2x+2x+1
-3x-11=-2 /+11
-3x=9 /:(-3)
x=-3
1 5 1